Depression and binge drinking in farm and non-farm rural adults in Saskatchewan, Canada - Bonnie Janzen; Chandima Karunanayake; Donna Rennie; Joshua Lawson; James Dosman; Punam Pahwa (James Cook University, 2020)
Introduction: Despite some attention paid to farm stress in the popular press, recent Canadian research examining the mental wellbeing of farming populations relative to other rural dwellers is sparse. International research on the topic has shown inconsistent findings and has mainly focused on men. The objective of the present study was to examine the correlates of mental health among rural Saskatchewan women and men, positioning farm/non-farm residence as a main explanatory variable, and depression and binge drinking as measures of mental health. Methods: The cross-sectional sample consisted of 1701 women (47.8% farm) and 1700 men (53.3% farm) who participated in the 2014 phase of the Saskatchewan Rural Health Study, a prospective cohort study primarily examining the respiratory health of rural people in the southern part of the province of Saskatchewan, Canada. Data were collected using mailed self-report questionnaires and included measures of mental health assessing health professional diagnosed depression and binge drinking, in addition to a broad array of demographic characteristics, stressors and resources. Multiple logistic regression was the primary method of analysis; generalized estimating equations were utilized to account for household clustering. All analyses were conducted separately for women and men and by mental health indicator. Results: Farm/non-farm residence was related to depression but only under particular circumstances, which in turn differed by gender. In women, non-farm residents with two or more chronic conditions reported more depression than their farm counterparts (odds ratio (OR)=2.62; 95% confidence interval (CI) 1.28-5.36); non-farm men with secondary school education reported greater depression than farm-dwelling men (OR=2.93; 95%CI 1.31-6.59). The remaining correlates of depression were generally consistent with previous research in rural populations, including younger age, being non-partnered (men only), higher stress, greater financial strain (women only) and lower social support (women only). Binge drinking was significantly elevated in non-farm women (OR=1.68; 95%CI 1.21-2.33) and non-farm men (OR=1.70; 95%CI 1.33-2.17) compared to the farming population. Among women only, not having access to a regular family doctor/nurse practitioner was associated with an increased likelihood of binge drinking (OR=2.05; 95%CI 1.13-3.71) compared to women perceiving better access. Conclusion: The present study is one of very few recently published quantitative studies of the correlates of mental health among farm and non-farm adults in rural Canada. The findings suggest that non-farm dwellers in rural Saskatchewan may be more vulnerable to compromised mental health than their farming counterparts. Additional research employing a longitudinal design and enhanced measurement is required to confirm or refute these findings.